Cross-Border Trade Malaysia-Indonesia: Involvement of Buton Early Immigrants - Siswanto, Hanif Abdurahman; Rudiatin, Endang (Universitas Muhammadiyah Jakarta, 2024)
Border trade in Sabah has occurred for centuries, extending back to pre-colonial times, and has progressed into economic integration, according to academia. In international relations, such border trade is defined as bottom-up border trade since it occurs naturally between two communities based on demand and supply rather than state involvement. This paper aims to discover cross-border trade practitioners beyond the border communities. This qualitative study adopts an inductive research strategy with unstructured interviews with four informants. This study found that early immigrants from Buton who migrated from Southeast Sulawesi to Sabah in the 1970s and early 2000s played an important role in maintaining and connecting border communities and consumers. Migrants carry out cross-border trading in Sabah between Indonesia and Malaysia. Border trade subsequently became not only a source of income for border communities but also a necessity for the survival of early immigrants, who until recently relied on border trading activities for commodity trading activities in the host country.